Comparative genomics of Staphylococcus epidermidis from prosthetic-joint infections and nares highlights genetic traits associated with antimicrobial resistance, not virulence. Issue 2 (13th February 2021) - Månsson, Emeli; Bech Johannesen, Thor; Nilsdotter-Augustinsson, Åsa; Söderquist, Bo; Stegger, Marc
Abstract : There is increased awareness of the worldwide spread of specific epidemic multidrug-resistant (MDR) lineages of the human commensal Staphylococcus epidermidis . Here, using bioinformatic analyses accounting for population structure, we determined genomic traits (genes, SNPs and k- mers) that distinguish S. epidermidis causing prosthetic-joint infections (PJIs) from commensal isolates from nares, by analysing whole-genome sequencing data from S. epidermidis from PJIs prospectively collected over 10 years in Sweden, and contemporary S. epidermidis from the nares of patients scheduled for arthroplasty surgery. Previously suggested virulence determinants and the presence of genes and mutations linked to antimicrobial resistance (AMR) were also investigated. Publicly available S. epidermidis sequences were used for international extrapolation and validation of findings. Our data show that S. epidermidis causing PJIs differed from nasal isolates not by virulence but by traits associated with resistance to compounds used in prevention of PJIs: β-lactams, aminoglycosides and chlorhexidine. Almost a quarter of the PJI isolates did not belong to any of the previously described major nosocomial lineages, but the AMR-related traits were also over-represented in these isolates, as well as in international S. epidermidis isolates originating from PJIs. Genes previously associated with virulence in S. epidermidis were over-represented in individual lineages, but failed to reach statistical significance when adjusted for population structure. Our findings suggest that the current strategies for prevention of PJIs select for nosocomial MDR S. epidermidis lineages that have arisen from horizontal gene transfer of AMR-related traits into multiple genetic backgrounds.